Before going to Constantinople. A few remarks on the preparation of the diplomatic mission of Stanisław Chomentowski, the voivode of Masovia, to the Ottoman Porte in 1712 - Perłakowski, Adam (Władza i polityka w czasach nowożytnych. Dyplomacja i sprawy wewnętrzne, 2020)
The purpose of Stanisław Chomentowski’s mission as the Grand Ambassador to the Sublime Porte in 1712–1714 was to confirm the terms of the Treaty of Karlowitz, signed in 1699, and to reduce the political tension between the Polish-Lithuanian Commonwealth and Turkey, which in late 1712 and throughout almost entire 1713 even threatened to erupt in an armed conflict between the two states. Considering the course of the mission, the difficulties in completing it, and even the temporary restriction of the Polish diplomat’s freedom on the territory of the Ottoman state, its results should be regarded as definitely positive. Chomentowski’s visit to Turkey, where he was supported by Augustus II’s other diplomats, Franciszek Goltz (starosta of Śrem) and Jan Spiegel, resulted in averting the Turkish threat and renewing the terms of the Treaty of Karlowitz. The three missions, conducted by Chomentowski, Spiegel and Goltz, should be studied in the context of Augustus II’s one large-scale diplomatic action, which ended successfully. It also proves that the work of the Polish diplomatic service in the times of the kings from the House of Wettin, about which historians, paradoxically, do not have a very high opinion to this day, was actually quite effective.